Identification of circulating Tfh/Th subsets as a biomarker of developed hospital-acquired pneumonia - Peng, Yuan; Tao, Tao; Yu, Ni-Wen; Xu, Chenyang; Chen, Cheng (Frontiers in Immunology, 2025)
BackgroundThis study aimed to explore the possible value of follicular helper T (Tfh) cells in hospital-acquired pneumonia (HAP).MethodsFlow cytometry was used to measure circulating Tfh and helper T cell (Th) cells in 62 HAP patients and 16 healthy individuals. HAP patients were further categorized into uncontrolled and controlled groups, in accordance with relevant guidelines. Subgroup analyses were additionally conducted based on the pathogen and the presence of bloodstream infections (BSIs) and the incidence of septic shock. Kaplan-Meier survival analysis and ROC analysis were performed to estimate the prognostic value of the combination of Tfh/Th ratios and PCT levels.ResultsThe Tfh/Th ratio was notably higher in uncontrolled HAP patients than in controls (P<0.05). Specifically, either the Klebsiella pneumoniae (K.p) -positive HAP or BSIs subgroups or septic shock subgroups showed significantly increased Tfh/Th ratios (P<0.05). PCT level in BSIs and septic shock subgroups was significantly increased. However, there were no significant differences in PCT level between K.p-infected and non-K.p-infected patients. So, the Tfh/Th ratio is a good supplement to PCT for distinguishing between the K.p and non-K.p groups. The Tfh/Th ratio also demonstrated a strong correlation with procalcitonin (PCT) levels (P<0.05). Accordingly, the combination of Tfh/Th and PCT could serve as a more effective predictive marker for HAP deterioration and survival prediction. HAP patients with a high Tfh/Th ratio along with high PCT levels had a lower 28-day survival rate.ConclusionThe circulating Tfh/Th ratio, instrumental in gauging the severity of patients with HAP, could be employed as a prognostic biomarker for HAP.